2010
DOI: 10.1016/j.jcp.2010.01.029
|View full text |Cite
|
Sign up to set email alerts
|

A gradient-augmented level set method with an optimally local, coherent advection scheme

Abstract: a b s t r a c tThe level set approach represents surfaces implicitly, and advects them by evolving a level set function, which is numerically defined on an Eulerian grid. Here we present an approach that augments the level set function values by gradient information, and evolves both quantities in a fully coupled fashion. This maintains the coherence between function values and derivatives, while exploiting the extra information carried by the derivatives. The method is of comparable quality to WENO schemes, b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 29 publications
(80 reference statements)
1
105
0
Order By: Relevance
“…al. demonstrated that for analytic flow fields the gradient augmented provides results comparable to higher-order WENO schemes at a lower computational cost [16]. Results for flows depending on derivatives of the level set function where not presented.…”
Section: Standard Gradientmentioning
confidence: 98%
See 2 more Smart Citations
“…al. demonstrated that for analytic flow fields the gradient augmented provides results comparable to higher-order WENO schemes at a lower computational cost [16]. Results for flows depending on derivatives of the level set function where not presented.…”
Section: Standard Gradientmentioning
confidence: 98%
“…Take To ensure that the level set and gradient field remain coupled throughout time Eqs. (2.4) and (2.5) are advanced in a coherent and fully coupled manner [16]. Lagrangian techniques are used to trace characteristics back in time to determine departure locations.…”
Section: Standard Gradientmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting method is approximately third order in the distance function for smooth interfaces [10]. A similar approach can be used in gradient augmented level set methods [18], where both φ and its gradient are defined at each grid point, in which case a type of Hermite interpolation defines a high-order approximation of the interface. This again requires a nonlinear minimisation method to find closest points for query points adjacent to the interface -reinitialisation methods for gradient augmented level set methods include that of [4], which is based in part on Chopp's quasiNewton method, and the method of [7], which follows the principles of the fast marching method by using Huygens' principle and Newton's method restricted to individual tetrahedrons.…”
Section: Motivation and Previous Workmentioning
confidence: 99%
“…In [10], the authors used an augmented level set (as described in [31]) in which they solve by finite difference schemes an advection equation for φ and an other one for ∇φ. Moreover, three equations are solved at reinitialization step to take into account the higher derivatives of φ.…”
Section: High Order Derivativementioning
confidence: 99%